Craticula widouensis, a new diatom (Bacillariophyta) species of a Sahelian temporary pond (North Senegal). Issue 2 (3rd April 2019) - Beauger, Aude; Wetzel, Carlos E.; Peiry, Jean-Luc; Voldoire, Olivier; Ector, Luc
ABSTRACT: During a floristic survey of temporal ponds in the Sahelian area of North Senegal, a new Craticula species (Bacillariophyceae) was discovered, and it is named here Craticula widouensis Beauger, C.E.Wetzel & Ector sp. nov . The new taxon is formally described using light and scanning electron microscopy. The species presents a unique set of morphological characteristics, including valve dimensions, outline, and presence of conspicuous elongated silica slats at the valve face/valve mantle junction and some narrow apically elongated struts irregularly distributed on the valve face, which make Craticula citrus (Krasske) E. Reichardt the most similar taxon to our knowledge. The ecological preferences of Craticula widouensis sp. nov. are eutrophic, contaminated, and hot ponds. A morphological comparison with the most similar species and a checklist of Craticula taxa are also presented.